Performance evaluation of pan position methods in domestic induction cooktops - Altintas, Nihan; Ozturk, Metin; Oktay, Ulas (SPRINGER, 2023)
The single-switch quasi-resonant inverter topology is typically favored for low-cost and low-output-power applications among the resonant inverters used in induction heating systems. Despite the low-cost advantage of the quasi-resonant inverter, the soft-switching range is quite narrow, and it is not stable depending on the electrical parameters of the load that is desired to be heated. In addition, to ensure safe operation in induction cookers, it is important to know the properties of the material from which the pan is made, the diameter of the pan, and the coverage ratio between the pan and the coil. Especially in the single-switch quasi-resonant topology, it is complicated to determine pan size and pan position compared to other topologies. On the other hand, closed-loop power control algorithms are essential for single-switch inverter applications. A big relationship exists between pan detection algorithms and closed-loop power control methods used. This study proposes six alternative methods of determining the pan-coil coverage ratio for the single-switch quasi-resonant topology used in domestic induction heating cooktops. Unlike state-of-the-art methods, the proposed methods do not increase the system's cost since they use the processor for power control, are not complicated, and provide ease of application. Each method is examined in a simulation environment and experimentally for different coverage rates and compared. As a result of the comparison, the diode conduction time method in single-switch quasi-resonant systems is the most appropriate regarding reliability and applicability.
Keywords: Coil pan coverage; Domestic induction cooktops; Single switch topology; Pan detection methods; RESONANT INVERTER; IDENTIFICATION; RECOGNITION; SYSTEMS; Engineering